INOVASI TEKNOLOGI UNTUK KONSERVASI SUMBERDAYA MINERAL: TANTANGAN DAN PELUANG - Mabruri, Ibnu (PERHAPI, 2024)
Technological innovation has become the key to improving mineral resource conservation worldwide. In this paper, we discuss the challenges and opportunities faced in developing technology for mineral resource conservation. One of the main challenges is the ever-increasing demand for mineral resources, which requires extraction technologies that are not environmentally friendly and can generate waste and pollution. However, efficient processing technology, mineral recovery and recycling technology, as well as the use of renewable energy in the mining industry, digital sensors and monitoring, and geographic information technology (GIS) have shown great benefits in reducing environmental impact and increasing resource use efficiency. In addition, appropriate policies and regulations, human resource skills enhancement, community awareness and acceptance, as well as mineral resource diversification and local community empowerment are also important factors in mineral resource conservation.